Pengaruh Tingkat Pendidikan, Pekerjaan Dan Pendapatan Keluarga Yang Mendapat Pendidikan Kesehatan Terhadap Penatalaksanaan Diet Diabetes Melitus Dalam Keluarga Di Rumah Sakit Umum Daerah Gambiran Kediri - Sucipto Sucipto (coba, 2012)
The effect of the level of education, job, and income that gets the health education on the management of the diet for the diabetes mellitus in a family. Unless Diabetes Mellitus (DM) is well-handled, it will affect the complication on the various vital organs of the human body. By well experiences such as the cooperation among patient, family and medical staff, the complication of DM can be prevented, or at least, can be slowly halted its development. To target the point, the participation of the patient, the family of the sufferer to care for is badly needed. The aim of the research is to know the effect of the level of education, job and income that gets the health education on the management of the diet for the diabetes mellitus in a family. The method of the research is the analytical descriptive method by using cross sectional approach. The research was applied in November 2008. The population are the family and the sufferers of the DM who were treated in the Gambiran Public Hospital in Kediri. The sample uses the purposive sampling, and the total of respondents is 60. The data collecting is questioner. The data is represented in pictures, tables and narrative. The analytical data with statistical Chi-square test is supposed to know the relation of the variables. Whereas, to know the effect of all, the independent variable and dependent variable use the logistic binary regressive analysis with SPSS Program version 12. The result of the research shows that the higher education probably reaches 3.4 times, the management of DM is much better than that of the lower education (OR = 3.369, CI = 0.728 – 15. 604), and the other factors that improve the management of the diet in family are jobs, incomes and ages. The research concludes that the level of education, job, income and age are the main factors to improve the management of the diet in family. The health guides (nutritionists) are advisably giving guidance in accordance with the backgrounds of education, job, income, and age of the target points.